2020
DOI: 10.3233/jad-201058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors of Alzheimer’s Disease Modulate How Diet is Associated with Long-Term Cognitive Trajectories: A UK Biobank Study

Abstract: Background: Fluid intelligence (FI) involves abstract problem-solving without prior knowledge. Greater age-related FI decline increases Alzheimer’s disease (AD) risk, and recent studies suggest that certain dietary regimens may influence rates of decline. However, it is uncertain how long-term food consumption affects FI among adults with or without familial history of AD (FH) or APOE4 (ɛ4). Objective: Observe how the total diet is associated with long-term cognition among mid- to late-life populations at-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…As described in the Methods Section, cross-sectional and interventional studies demonstrated the associations of cheese intake in general or cheese of certain types with lower or decline in BP, and meta-analyses demonstrated the associations of cheese intake with measures that are closely relevant to BP, such as stroke risk, arterial stiffness, and blood lipid [16,17,19,20,42]. In addition, using the same UK Biobank data, a greater cheese intake was shown to be associated with a greater longitudinal retention (less decline) in fluid intelligence [43]. We further demonstrated that greater cheese intake is associated with a greater retention of visuospatial memory performance, whereas previous studies failed to show this, possibly due to limited sample size [44].…”
Section: Discussionmentioning
confidence: 98%
“…As described in the Methods Section, cross-sectional and interventional studies demonstrated the associations of cheese intake in general or cheese of certain types with lower or decline in BP, and meta-analyses demonstrated the associations of cheese intake with measures that are closely relevant to BP, such as stroke risk, arterial stiffness, and blood lipid [16,17,19,20,42]. In addition, using the same UK Biobank data, a greater cheese intake was shown to be associated with a greater longitudinal retention (less decline) in fluid intelligence [43]. We further demonstrated that greater cheese intake is associated with a greater retention of visuospatial memory performance, whereas previous studies failed to show this, possibly due to limited sample size [44].…”
Section: Discussionmentioning
confidence: 98%
“…In a recent case-control study by Filippini et al [32], associations between cheese intake and dementia outcomes were not found. Nonetheless, a beneficial association between cheese intake and cognitive performance is supported in the majority of previous studies [33][34][35][36]. For potential explanations for the better cognitive performance, the probiotic effect of lactid acid bacteria through the gut-brain axis [36], high level of vitamin K2 [36], and role of bioactive compounds [34] and the amino acid tyramine [33] that are high in cheese have been discussed.…”
Section: Discussionmentioning
confidence: 98%
“…In general, the evidence between dairy intake and dementia outcomes or cognitive performance is incoherent [6,7,37,38] and may be product specific [33][34][35][36]39]. Two systematic reviews have suggested that higher dairy intake may have a beneficial association with cognitive performance [37,38], but it may be limited to Asian populations [38].…”
Section: Discussionmentioning
confidence: 99%
“…This database comprised data on 10,894,596 dementia-associated SNPs from 26,757 maternal AD dementia cases. In this data, the AD/dementia was mainly defined as the AD dementia syndrome, which belongs to the anamnestic syndrome of hippocampal type, with the relevant decline in memory, executive function, attention, word-finding, spatial cognition ( Karantzoulis and Galvin, 2011 ); ( Klinedinst et al, 2020 ). Besides, the United Kingdom biobank study reported the genetic risk factor rooted in AD dementia, such as apolipoprotein E ε4 allele (APOE4), and a parental family history of AD dementia.…”
Section: Methodsmentioning
confidence: 99%